Searches for Large-Scale Anisotropy in the Arrival Directions of Cosmic Rays Detected above Energy of 1019 eV at the Pierre Auger Observatory and the Telescope Array - Almela, Daniel Alejandro; Asorey, Hernán Gonzalo; Bertou, Xavier Pierre Louis; Dasso, Sergio Ricardo; Dova, Maria Teresa; Etchegoyen, Alberto; Figueira, Juan Manuel; Filevich, Alberto; Garcia, Beatriz Elena; Gomez Berisso, Mariano; González, Nicolás Martín; Guardincerri, Yann; et al. (Iop Publishing, 2014)
Fil: Almela, Daniel Alejandro. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Instituto de Tecnologías en Detección y Astropartículas. Subsede del Instituto de Tecnologías en Detección y Astropartículas Mendoza; Argentina